(untitled) (Biological Sciences - PJSIR, 1996)
Foaming/whipping agent has been prepared from soybean meal using different proteolytic enzymes i.e. Alcalase, Neutrase, Papain and Pepsin. Optimum conditions such as time, temperature, pH of the reaction mixture have been worked out. The foaming agent prepared by the treatment of Pepsin on soybean meal possesses maximum whipping expansion and foam stability. The product is in powder form and possesses a good storage life upto two years.